Macrofossil data from selected samples of the Last Glacial at Füramoos, Southern Germany - Oliver A Kern (PANGAEA, 2021)
Macrofossil data from selected samples of the MIS 2-4 period from Füramoos, Southern Germany. The data are used to augment the palynological dataset of the same study.